ChemInform Abstract: Access to Congested Quaternary Centers by Pd‐Catalyzed Intermolecular γ‐Arylation of Unactivated α, β‐Unsaturated Aldehydes. Issue 45 (14th October 2013) - Franzoni, Ivan; Guenee, Laure; Mazet, Clement
Abstract A general, simple, and easy scalable method for the γ‐arylation of a variety of α, β‐unsaturated aldehydes with aryl bromides is developed.